FEATURES OF THE USE OF DIGITAL TECHNOLOGIES IN THE EDUCATIONAL PROCESS OF PROFESSIONAL (VOCATION-TECHNICAL) EDUCATION INSTITUTIONS (Innovative professional education, 2024)
Modern society is characterized by a significant impact of information technologies on all spheres of human life. In a special way, the processes of digital transformation affect educational institutions, including vocational and technical (vocational and technical). Currently, professional (vocational and technical) education occupies an important place in the country's economy, determining the priority of effective training of highly qualified personnel in the state policy of Ukraine.
Keywords: professional education, information technologies, educational process